Pengaruh Minat Belajar dan Keaktifan Belajar Siswa Terhadap Prestasi Belajar Siswa Pada Mata Pelajaran Ekonomi Kelas X-B SMA Swasta Nusantara - Charles Fransiscus Ambarita; Diana Naibaho (STKIP Subang, 2026)
This study aims to examine the impact of learning interest and learning activeness on students’ academic achievement. A quantitative approach with a causal associative design was employed. The subjects of this study consisted of 30 students from class X-B at SMA Swasta Nusantara in the 2025/2026 academic year. Data were collected using questionnaires to measure learning interest and learning activeness, while academic achievement data were obtained through documentation. The data analysis technique used was multiple linear regression, following the fulfillment of validity, reliability, and classical assumption tests. The findings reveal that: (1) learning interest has a positive and significant effect on academic achievement (sig. 0.000 < 0.05); (2) learning activeness also has a positive and significant effect on academic achievement (sig. 0.000 < 0.05); and (3) simultaneously, learning interest and learning activeness have a significant effect on academic achievement, as indicated by an F-value of 76.486 with a significance level of 0.000 (< 0.05). The coefficient of determination (R²) is 0.845, meaning that 84.5% of the variance in academic achievement can be explained by these two independent variables. In conclusion, learning interest and learning activeness play a crucial role in enhancing students’ academic achievement.